Adaptation of care for non-communicable diseases during the COVID-19 pandemic: a global case study. (7th July 2022) - Miller, Laura; Alani, Ahmad Hecham; Avril, Nicolas; Jingree, Muksha Luxmi; Atwiine, Aston B; Al Amire, Khaldoun; Khan, Mushtaq; Moe, Aye Aye; Nyalwal, Beatrice Lydiah Adhiambo; Mohamed, Abdirashid Adan; Ruto, Titus Kiprono; Kiapi, Lilian
Abstract : People living with non-communicable diseases (PLWNCDs) are at greater risk of severe COVID-19 illness. This case study highlights the adaptations that were made to humanitarian health programmes in five countries to reduce exposure risk for PLWNCDs during the COVID-19 pandemic. Common adaptations included facility-level administrative and engineering controls, improved triaging, change in prescribing practices, decrease in frequency of stable patient visits, shift to remote consultations and expanded scope of responsibility for existing community health workers. Despite fears of the impact on health service utilisation, PLWNCDs continued to seek services and changes in utilisation rates between the pre-COVID-19 and COVID-19 periods were attributed more to factors like population changes, COVID-19 travel restrictions, closure of other health services, and enhanced health education and community engagement. This study highlights the resilience and creativity of frontline health staff and managers, and their ability to make quick shifts in service delivery modalities in response to changes in risk for client groups in accordance with the evolving contextual reality. Other contextual changes such as infectious disease outbreaks, conflicts and natural disasters happen regularly within humanitarian settings, and specific groups are often more at risk. With more specific information about risks for different client groups, targeted approaches can be done to ensure that those most at risk of a specific threat are able to ensure access to sustained services.